1991
DOI: 10.1021/jf00001a006
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the dissociation of .beta.-conglycinin into subunits by heat treatment

Abstract: A heat-induced transparent solution consisting of dissociates can be prepared under appropriate conditions: 8-conglycinin preparations, pH, and salt affected the thermal dissociation. Experimental conditions studying quantitative dissociation into subunits and analyzing the dissociation process using gel filtration without artifact are examined. P-Conglycinin dissolved in distilled water (0.5 ?6 w/v, pH 7.5) can be heated without turbidity even at 100 "C for 30 min. The elution buffer, 3.2 mM potassium phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
6
23
0
Order By: Relevance
“…Although qualitative, the results in Table 2 gave further evidence that when the repulsive negative charges from vicilin 2°were "removed", the protein was able to gel at lower concentrations. Similarly, when solutions of only 0.5% (w/v) -conglycinin were heated at pH 7.5, no aggregate formation was detected unless salt was added (25), even though (as we showed here for vicilin) the protein denatured and exposed its hydrophobic residues. The authors, as we are doing here, suggested that mutual repulsion of the hydrophilic domains was superior to the hydrophobic interaction and, thus, inhibited aggregation.…”
Section: Discussionsupporting
confidence: 61%
“…Although qualitative, the results in Table 2 gave further evidence that when the repulsive negative charges from vicilin 2°were "removed", the protein was able to gel at lower concentrations. Similarly, when solutions of only 0.5% (w/v) -conglycinin were heated at pH 7.5, no aggregate formation was detected unless salt was added (25), even though (as we showed here for vicilin) the protein denatured and exposed its hydrophobic residues. The authors, as we are doing here, suggested that mutual repulsion of the hydrophilic domains was superior to the hydrophobic interaction and, thus, inhibited aggregation.…”
Section: Discussionsupporting
confidence: 61%
“…For example, in the case of emulsions stabilized using SPI 1 the mean HCT increased from 8.31 min at pH 6.4 to 12.17 min at pH 7.5. The pH-dependent trends in HCTs in these emulsion results are consistent with those found by Hermansson (1977), Hermansson (1978), Iwabuchi, Watanabe, and Yamauchi (1991), Mohamed and Xu (2003) and Ryan et al (2008), where intact soy protein dispersions were found to be more heat stable at alkaline than at acidic pH. Nagano, Mori, and Nishinari (1994) also reported that lowering the pH caused the denaturation temperature of SPI, glycinin and b-conglycinin to shift to lower values which may, in part, also explain the results obtained.…”
Section: Heat Coagulation Time (Hct) Of Model Emulsionssupporting
confidence: 88%
“…These complexes depend largely on the electrostatic atmosphere surrounding protein molecules; formation of complexes occurs more randomly and larger complexes are formed under systems containing NaCl (Kitamura et al, 1974;Utsumi et al, 1984;Utsumi and Kinsella, 1985;Iwabuchi et al, 1991). The failure of the ionexchange technique to separate the globulin fraction might be related to the likely association of 7 S-and 11 S-like subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The 7 S-and 11 S-rich fractions have been prepared and purified from pea and soybean proteins by different chromatographic techniques: gel filtration, ion-exchange (Gueguen et al, 1984;Iwabuchi et al, 1991), and affinity chromatography (Kitamura et al, 1974).…”
Section: Introductionmentioning
confidence: 99%